Prefácio - Oliveira Júnior, José Alcebíades; Lima Marques, Claudia; Machado, Gustavo Castagna; Sontag, Kenny; de Oliveira, Mariana Kuhn; Feloniuk, Wagner Silveira; Cortese, Vicente de Azevedo Bastian (Cadernos do Programa de Pós-Graduação em Direito – PPGDir./UFRGS, 2016)
Prefácio ao Volume XI, Número 1, Ano 2016